The city in American literature and culture - McNamara, Kevin R., 1958- (New York : Cambridge University Press, 2021)
"The city's "Americanness" has been disputed from the time of Jefferson's struggle with Hamilton over the new nation's character and its future. At another peak of antiurban sentiment, this volume brings literary and cultural history and criticism to bear on city lives and spaces, engaging a history of promise and struggle as represented literature, film, and visual arts. Drawing on social science to define the urban condition, but as literature does, focusing on the representation and interpretation of experience, the chapter's authors examine the effects of the large and local forces shaping cities and their denizens' lives, and the street-level activity that remakes cultures and group and individual identities. They examine, among other things, city life under conditions of marginalization, uprooting, precarity and, anonymity in the industrial and post-industrial city; and how people construct lives, cultures, and identities within and against the constraints of urban society, as well as by grasping the opportunities to remake the city. The final suite of essays brings the represented city into conversation with contemporary theory allowing each to test the terms of the other"--
Includes index.
Keywords: American literature -- History and criticism; Cities and towns in literature; City and town life in literature; Cities and towns -- Social aspects -- United States; Cities and towns -- Political aspects -- United States; LITERARY CRITICISM / American / General; LITERARY CRITICISM / American / General